2014
DOI: 10.17221/132/2013-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Response of Vicia species to Ascochyta fabae and Uromyces viciae-fabae

Abstract: Sillero J.C., Rubiales D. (2014): Response of Vicia species to Ascochyta fabae and Uromyces viciae-fabae. Czech J. Genet. Plant Breed., 50: 109-115.A collection of 267 accessions belonging to 61 Vicia species other than V. faba was screened under growth chamber conditions for response to Ascochyta fabae and Uromyces viciae-fabae, causal agents of ascochyta blight and faba bean rust, respectively. High resistance to both diseases was very frequently detected in Vicia spp. in contrast to the high susceptibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
4
0
3
Order By: Relevance
“…Our essay is the first research work carried out in Algeria on this topic, that it is based on the research of the sources of resistance of seven (07) varieties of faba bean (Giza 02, Giza 40, Sakha 01, Sakha 02, Sakha 03, Ziban and Precoce of Seville), against the chocolate spot disease caused by Botrytis fabae Sard. A similar study was carried out in Spain by Madeira et al (1993) and Sillero and Rubiales (2014), in Poland by Goral and Walentyn-Goral, 2012 and in Morocco by Bouhassan et al 2004b. A significant difference was observed in the reaction of faba bean varieties against two strains of Botrytis fabae, by 04 susceptible varieties (Giza02, Sakha01, Sakha02 and Sakha03), two tolerant varieties (Giza40 and Ziban) and only one resistant variety (Precoce de Seville). This difference has been reported in some studies around the world with other faba bean cultivars (Villegas-Fernandez et al, 2012;Wolde and Mitiku, 2018;Abd-Rabh et al, 2013;Bouhassan et al, 2004a,b;Terefe et al, 2015).…”
Section: Discussionmentioning
confidence: 55%
“…Our essay is the first research work carried out in Algeria on this topic, that it is based on the research of the sources of resistance of seven (07) varieties of faba bean (Giza 02, Giza 40, Sakha 01, Sakha 02, Sakha 03, Ziban and Precoce of Seville), against the chocolate spot disease caused by Botrytis fabae Sard. A similar study was carried out in Spain by Madeira et al (1993) and Sillero and Rubiales (2014), in Poland by Goral and Walentyn-Goral, 2012 and in Morocco by Bouhassan et al 2004b. A significant difference was observed in the reaction of faba bean varieties against two strains of Botrytis fabae, by 04 susceptible varieties (Giza02, Sakha01, Sakha02 and Sakha03), two tolerant varieties (Giza40 and Ziban) and only one resistant variety (Precoce de Seville). This difference has been reported in some studies around the world with other faba bean cultivars (Villegas-Fernandez et al, 2012;Wolde and Mitiku, 2018;Abd-Rabh et al, 2013;Bouhassan et al, 2004a,b;Terefe et al, 2015).…”
Section: Discussionmentioning
confidence: 55%
“…In a recent host pathogenicity test also, it is confirmed that faba bean isolates of D. fabae were specific to Vicia faba (Sillero and Rubiales 2014). Farr and Rossman (2017).…”
Section: Didymella Fabaementioning
confidence: 82%
“…J. Schröt. je uzročnik rđe grahorica i pasulja i ima širok krug domaćina koje može da inficira i to su biljne vrste iz rodova Pisum, Lathyrus and Lens (Sillero and Rubiales, 2014). Na semenu grahorica utvrđene su dve vrste iz roda Fusarium, F. verticillioides i F. proliferatum (Miličević i sar., 2013).…”
Section: Rezime Uvodunclassified
“…Isto tako prouzrokovači bolesti kao što su Erysiphe pisi, Botrytis cinerea, Rhizoctonia solani, Cercospora medicaginis, Pseudopeziza medicaginis, Sclerotinia trifoliorum, Stemphylium botryosum, Verticillium albo-atrum, Aphanomyces euteiches kao i vrste iz roda Phytium, Leptosphaerulina, Phoma, Phythophthora i Alternaria su značajni prouzrokovači bolesti grahorice, rašreni u svim arealima njenog gajenja (Morgan and Johnson, 1965;Stovold and Walker, 1980;Hughes and Grau, 2007;Villegas-Fernández and Rubiales, 2011;Salam et. al., 2011;Sillero et al, 2014).…”
Section: Rezime Uvodunclassified
See 1 more Smart Citation